Genome Analysis of Goose-Origin Astroviruses Causing Fatal Gout in Shanghai, China Reveals One of Them Belonging to a Novel Type Is a Recombinant Strain - Quan Shen; Zi Zhuang; Juan Lu; Lingling Qian; Guangquan Li; Aaron Gia Kanton; Shixing Yang; Xiaochun Wang; Huiying Wang; Jun Yin; Wen Zhang (Frontiers in Veterinary Science, 2022)
Since 2014, a goose-origin astroviruses disease, which is characterized by urate precipitation in viscera, has rapidly spread to major commercial goose provinces leading to huge economic losses in the poultry industry of China. In March 2020, a goose farm locates in Shanghai, China, where there was no goose astroviruses (GAstVs) infection reported before, experienced an outbreak of gout disease in geese. The etiological investigation was carried out by virus metagenomics and bacterial culture and two GAstVs strains, designated as CHSH01 and CHSH02, were determined. Their complete genomes were measured to 7,154 and 7,330 nt in length, excludingthe poly(A) tail, respectively, and had different genomic features and classifications. CHSH01 shared a very low sequence identity with other strains in terms of not only the complete genome but also different ORFs. Phylogenetic analysis showed CHSH02 belonged to GAstV-2, which was the predominant species in the geese with gout in China according to the previous study. Meanwhile, CHSH01 strain displayed low identity with other AstVs, and phylogenetic and recombination analysis suggested that CHSH01 belonging to a novel type was a recombinant strain, one parent strain of which was an AstV determined from a bar-headed goose (a kind of migrant bird). Moreover, the primary epidemiological investigation showed that the two strains were prevalent in the same goose farm and co-infection occurred. These findings arise the potential cross-species transmission of CHSH01 between domestic and wild fowl.